Changing Cultural Spaces, Transformation of the Traditions: Hıdırellez Celebrations held in Ankara and Hamamönü Hıdırellez Festivals - Selcan Gürçayır, Teke (Koc University, Vehbi Koc Ankara Studies Research Center (VEKAM), 2018)
Hıdırellez festival, one of the rituals that hails the start of summer, is celebrated widely across Anatolia. The belief thatwishes for the future will come true if certain actions are performed at Hıdırellez festival, may be seen as the basic motivation behind this ritual and the transmission of this tradition from generation to generation. Many practices at Hıdırellez are related to nature. The space to celebrate Hıdırellez is of the utmost importance due to the context of the ritual. There are many cultural spaces in Anatolia assigned for the celebration of Hıdırellez; these are selected based on the belief that they have been visited by Hızır. The cultural transmission of Hıdırellez celebrations is being hindered among an urbanizing population due to fewnew spaces being planned for them and a lack of protection for the existing spaces. This article focuses on the Hıdırellez festival spaces and the necessity of moving these spaces into cities in order to maintain the tradition. This article evaluates the basic importance of these spaces from the standpoint of sustainability and the formation of the tradition using the Hamamönü Hıdırellez festival, which is celebrated in Ankara. It discusses the variations of the participant profiles at the Sixth Hamamönü Hıdırellez festival, to be held in Ankara this year and the how their expectations have been shaped based on changing spaces. It concludes that besides the dimension of belief in the rituals, the dimension of entertainment is also prominent for participants at the Hamamönü Hıdırellez festival, and that various Hıdırellez traditions have found their way into popular culture.